2018
DOI: 10.1159/000494921
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light Treatment on Sleep, Cognition, Mood, and Behavior in Alzheimer’s Disease: A Systematic Review

Abstract: Background: Bright light treatment is a therapeutic intervention mainly used to treat sleep and circadian disturbances in Alzheimer’s disease (AD) patients. Recently, a handful of studies also focused on the effect on cognition and behavior. Conflicting findings are reported in the literature, and no definite conclusions have been drawn about its specific therapeutic effect. Summary: The aim of this review is to provide a critical evaluation of available evidence in this field, highlighting the specific charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(59 citation statements)
references
References 66 publications
1
57
0
1
Order By: Relevance
“…Studies specifically intervening on circadian rhythms that take into account the 24-h activity rhythm remain scarce. A number of studies have reported reduced circadian disruption after bright light therapy in patients with dementia [80], Parkinson's disease [81], depression [82], cardiovascular disease [83], and cancer [84]. However, it is largely unknown to what extent intervening on circadian factors and, subsequently 24-h activity rhythms, improves relevant clinical outcomes such as disease progression or mortality.…”
Section: Research Agendamentioning
confidence: 99%
“…Studies specifically intervening on circadian rhythms that take into account the 24-h activity rhythm remain scarce. A number of studies have reported reduced circadian disruption after bright light therapy in patients with dementia [80], Parkinson's disease [81], depression [82], cardiovascular disease [83], and cancer [84]. However, it is largely unknown to what extent intervening on circadian factors and, subsequently 24-h activity rhythms, improves relevant clinical outcomes such as disease progression or mortality.…”
Section: Research Agendamentioning
confidence: 99%
“…Its e cacy for depression and fatigue has also been reported in other medical and psychiatric conditions. For example, a recent review suggested that bright light therapy was effective for seasonal and non-seasonal depression and depression in dementia [39]. In addition, another systematic review also found that bright light therapy combined with psychosocial therapies was ranked the best in reducing cancer-related fatigue [40].…”
Section: Discussionmentioning
confidence: 99%
“…The positive effect of light is also found in previous research. A recent systematic review of Mitolo et al (2018) on the effects of light treatment describe some studies that show some effect of bright light therapy on the reduction of agitation in people with dementia (Burns et al, 2009;Lovell et al, 1995;Mishima et al, 1994). Figueiro et al have shown the positive effect of light exposure in several studies (2014, 2015 & 2016).…”
Section: Discussionmentioning
confidence: 99%